Mining elite loci and candidate genes for root morphology-related traits at the seedling stage by genome-wide association studies in upland cotton (Gossypium hirsutum L.) - Huaxiang Wu; Xiaohui Song; Muhammad Waqas-Amjid; Chuan Chen; Dayong Zhang; Wangzhen Guo (Journal of Integrative Agriculture, 2024)
Root system architecture plays an essential role in water and nutrient acquisition in plants, and it is significantly involved in plant adaptations to various environmental stresses. In this study, a panel of 242 cotton accessions was collected to investigate six root morphological traits at the seedling stage, including main root length (MRL), root fresh weight (RFW), total root length (TRL), root surface area (RSA), root volume (RV), and root average diameter (AvgD). The correlation analysis of the six root morphological traits revealed strong positive correlations of TRL with RSA, as well as RV with RSA and AvgD, whereas a significant negative correlation was found between TRL and AvgD. Subsequently, a genome-wide association study (GWAS) was performed using the root phenotypic and genotypic data reported previously for the 242 accessions using 56,010 single nucleotide polymorphisms (SNPs) from the CottonSNP80K array. A total of 41 quantitative trait loci (QTLs) were identified, including nine for MRL, six for RFW, nine for TRL, 12 for RSA, 12 for RV and two for AvgD. Among them, eight QTLs were repeatedly detected in two or more traits. Integrating these results with a transcriptome analysis, we identified 17 candidate genes with high transcript values of transcripts per million (TPM)≥30 in the roots. Furthermore, we functionally verified the candidate gene GH_D05G2106, which encodes a WPP domain protein 2 in root development. A virus-induced gene silencing (VIGS) assay showed that knocking down GH_D05G2106 significantly inhibited root development in cotton, indicating its positive role in root system architecture formation. Collectively, these results provide a theoretical basis and candidate genes for future studies on cotton root developmental biology and root-related cotton breeding.